Acarbose Use and Liver Injury in Diabetic Patients With Severe Renal Insufficiency and Hepatic Diseases: A Propensity Score-Matched Cohort Study - Chao, Chia-Ter; Wang, Jui; Huang, Jenq-Wen; Chien, Kuo-Liong (Frontiers in Pharmacology, 2018)
Background: Acarbose has been deemed contraindicated in diabetic patients with chronic kidney disease (CKD) or end-stage renal disease (ESRD), but such use is not uncommon. We tested whether this concept hold true in this population with different background hepatic diseases. Methods: All incident diabetic patients (n = 2,036,531) with stage 5 CKD/ESRD were enrolled from Taiwan between 2017 and 2013 and divided into those without chronic liver disease (CLD), with CLD but without cirrhosis, and those with cirrhosis. Among each group, acarbose users, defined as cumulative use > 30 days within the preceding year, were propensity-score matched 1:2 to non-users. Our main outcome was the development of liver injury events during follow-up Results: Acarbose users did not exhibit an increased incidence of liver injury during follow-up compared to non-users (hazard ratio and 95% confidence interval, 1.04 [0.88-1.25], 0.97 [0.61-1.56], and 0.71 [0.33-1.54] among those without CLD, with CLD but without cirrhosis, and those with cirrhosis, respectively), after adjusting for demographic profiles, comorbidities, potentially hepatotoxic medication use, and diabetic severity. Conclusions: The incidence of liver injury did not increase significantly among diabetic acarbose users with severe renal insufficiency than non-users, regardless of the presence or absence of chronic liver disease. Our findings support the renaissance of acarbose as a useful adjunct in diabetic patients with stage 5 and 5D chronic kidney disease.